Beginning x64 assembly programming : from novice to AVX professional - Hoey, Jo Van (Apress, 2019)
Teaching you how to program in assembly starting with simple and basic programs, all the way up to AVX programming, this book will enable you to write and read assembly code, mix assembly with higher level languages, know what AVX is, and a lot more than that. --